Análise proteômica da levedura Saccharomyces cerevisiae CAT-1 cultivada em diferentes concentrações de sacarose - Azarias, Gabriela de Sá [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Bacause of the national and international increasing demand for fuel ethanol, the alcohol industry needs more studies to benefit productivity without exacerbated increased investment. Therefore, it is necessary biochemical and physiological knowledge of the microorganisms and optimization of the medium and fermentation conditions. The proteomic analysis proposed in this work is a key tool in the elucidation of the changes suffered by the microorganism when exposed to adversity as, for example, aeration difficulty, low pH maintenance and sugar content of the mash and variations in molasses according to the harvest, recurrent situations in industrial fermentation processes. So, the aim of this study was to investigate the biochemical changes suffered by Saccharomyces cerevisiae CAT-1 grown by 30% (very high gravity fermentation) and 14% (high gravity fermentation) sucrose concentration. The analysis were performed by two-dimensional electrophoresis followed by mass spectrometry (MALDI-TOF/TOF). The results showed the presence of 22 differential protein spots between the two conditions with regard to quantitative analysis, qualitative and statistics analysis. Four of these spots were sequenced and correspond to GRX1p, Rtc3p, ENO2p and ADH1p. Additionally, the invertase activity was analyzed for understanding the catabolite repression and the enzyme activity reached its peak in 10 h in cultures containing 30% sucrose (13.68 ± 2,26U.ml-1). The ethanol yield and cell viability analysis showed that cultures containing 30% sucrose show advantageous results when compared to cultures containing 14% sucrose, once these cultures provided an ethanol yield of 15.99% and 99.2% viable cells at the end of each fermentation, very close to the theoretical values expected for an industrial process. Biomass and reducing sugars were also quantified.

Com a crescente demanda nacional e internacional de bioetanol combustível a indústria alcooleira carece de mais estudos que possam beneficiar a produtividade sem que haja aumento exacerbado de investimentos. Para tanto, faz-se necessário conhecimento bioquímico e fisiológico dos microrganismos, bem como otimização do meio de cultivo e das condições fermentativas. A análise proteômica, proposta neste trabalho, é uma ferramenta chave na elucidação das alterações sofridas pelo microrganismo quando exposto a adversidades como, por exemplo, dificuldade de aeração, baixa manutenção do pH e variações de teor de sacarose no mosto e no melaço de acordo com cada safra, casos recorrentes nos processos fermentativos industriais. Sendo assim, foi objetivo deste trabalho investigar as alterações bioquímicas sofridas por Saccharomyces cerevisiae linhagem CAT-1 cultivada em 30% (very high gravity fermentation) e 14% (high gravity fermentation) de concentração de sacarose. As análises foram realizadas por eletroforese bidimensional, seguida por espectrometria de massa (MALDI-TOF/TOF). Os resultados demonstram a presença de 22 spots protéicos diferenciais entre as duas condições no que diz respeito às análises quantitativas, qualitativas e estatísticas, dentre os quais quatro foram seqüenciados e correspondem às proteínas GRX1p, Rtc3p, ENO2p e ADH1p. Adicionalmente, a atividade invertásica foi analisada para a compreensão da repressão catabólica, sendo que a atividade enzimática atingiu seu pico de produção no tempo de 10h em cultivos contendo 30% de sacarose (13,68 ± 2,26U.ml-1). As análises de rendimento etanólico e viabilidade celular demonstram que cultivos contendo 30% de sacarose apresentam resultados vantajosos frente aos cultivos contendo 14% de sacarose, uma vez que proporcionaram um rendimento alcoólico de 15,99% e 99,2% de células viáveis ao final de cada...
Keywords: Proteômica; Levedos; Etanol; Fermentação; Microbiologia industrial; Ethanol